PENGEMBANGAN MATERI INTERNET OF THINGS UNTUK ANAK BERKEBUTUHAN KHUSUS MENGGUNAKAN LEGO DAN ELECFREAKS NEZHA KIT - Sebastian, Danny; Restyandito; Nugroho, Justinus Putranto Agung (Servirisma, 2025)
The low interest in learning among Indonesian students is a major challenge in the world of education. Uninteresting teaching methods often make students lose their motivation to learn. Therefore, the development of innovative and interactive Internet of Things (IoT) learning materials using LEGO Education and Elecfreaks NEZHA Kit, especially for children with special needs, is the main focus of this activity. This activity involved three lecturers from Duta Wacana Christian University and a team of teachers from the Robotics Education Center (REC) Yogyakarta branch. The results of the activity showed that the use of LEGO Education and Elecfreaks NEZHA Kit was effective in increasing students' interest in learning, developing critical thinking skills, problem solving, and collaboration. Challenges in implementation include the limited number of sensors and actuators and the need for material adjustments. Suggestions for further development include the addition of sensors and actuators, ongoing training for teachers, and regular evaluation of learning materials. In addition, this activity also provides recommendations for improving the quality of teaching through ongoing training for teachers and regular evaluation of the learning materials that have been developed. Thus, it is hoped that a more inclusive and adaptive learning environment can be created for children with special needs, as well as improving the overall quality of education.